Cultural appropriateness of post Sidr housing reconstruction : a case of Sharankhola, Bagerhat - Ghani, Shams Mansoor (BRAC University, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2018.